Principal Components Analysis of EEG Signals for Epileptic Patient Identification - Maria Camila Guerrero; Juan Sebastián Parada; Helbert Eduardo Espitia (Computation, 2021)
According to the behavior of its neuronal connections, it is possible to determine if the brain suffers from abnormalities such as epilepsy. This disease produces seizures and alters the patient’s behavior and lifestyle. Neurologists employ the electroencephalogram (EEG) to diagnose the disease through brain signals. Neurologists visually analyze these signals, recognizing patterns, to identify some indication of brain disorder that allows for the epilepsy diagnosis. This article proposes a study, based on the Fourier analysis, through fast Fourier transformation and principal component analysis, to quantitatively identify patterns to diagnose and differentiate between healthy patients and those with the disease. Subsequently, principal component analysis can be used to classify patients, employing frequency bands as the signal features. Besides, it is made a classification comparison before and after using principal component analysis. The classification is performed via logistic regression, with a reduction from 5 to 4 dimensions, as well as from 8 to 7, achieving an improvement when there are 7 dimensions in the precision, recall, and <semantics>F1</semantics> score metrics. The best results obtained, without PCA are: precision <semantics>0.560</semantics>, recall <semantics>0.690</semantics>, and <semantics>F1</semantics> score <semantics>0.620</semantics>; meanwhile, the best values obtained using PCA are: precision <semantics>0.734</semantics>, recall <semantics>0.787</semantics>, and <semantics>F1</semantics> score <semantics>0.776</semantics>.